Conversion prevention in high alumina cement products. - Ding, Jian. (University of Ottawa (Canada), 1995)
Mechanisms of stratlingite (C$\rm\sb2ASH\sb8)$ formation in the high alumina cement (HAC)--siliceous material--water systems were investigated. Different siliceous materials, e.g. natural zeolites, silica fume, fly ash, ground granulated blast-furnace slag, and different sodium salts, e.g. sodium silicate, sodium sulfate, etc. were employed. Reactions between CAH$\sb $ or C$\rm\sb2AH\sb8$ and dissolved silica occur. Acceleration of the silica dissolution by addition of chemical admixtures promoted the formation of stratlingite. A method for prevention of strength reduction of HAC products due to the conversion of thermodynamically unstable hexagonal calcium aluminates to cubic hydrogarnet is described. New conversion-preventing additives (CPA) to inhibit hydrogarnet formation in HAC products are described. Compressive strength development of HAC mortars containing the CPA additive was studied. The effect of curing conditions on strength development was also investigated. No strength reduction occurs for the HAC/CPA mortar water-cured at 38$\sp\circ$C. Stratlingite preferentially formed in the HAC paste containing the CPA additive. Durability of inhibited HAC products is also studied. Conversion inhibited high alumina cement binders have excellent characteristics for corrosion protection of reinforcement under severe test conditions. The HAC/CPA mortar can effectively resist the penetration of chloride ions. (Abstract shortened by UMI.)
Keywords: Engineering, Civil.